A STUDY ON THE EFFECT OF ANTIEPILEPTIC DRUGS ON SERUM LIPID PROFILE AND CAROTID ARTERY INTIMA MEDIA THICKNESS IN CHILDREN BETWEEN 1 TO 12 YEARS.: A STUDY ON THE EFFECT OF ANTIEPILEPTIC DRUGS ON SERUM LIPID PROFILE AND CAROTID ARTERY INTIMA MEDIA THICKNESS IN CHILDREN BETWEEN 1 TO 12 YEARS. - M, GOPI SRIKANTH; N, ARUNA DEVI; MOHAN C, CHANDRA; K, SOURIS; K, MRUDHULA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Epilepsy is among the commonly prevalent non communicable disease, particularly related to Central nervous system (CNS). The cumulative lifetime incidence of epilepsy is 3% and more than half of the cases begin in childhood. Seizures are common in pediatric age group and occur in approximately 10% of children. Epilepsyrequires long term anti-convulsanttreatment. The overall aim in the treatment of epilepsy should be complete control of seizures and no adverse reaction due to medication with an optimal quality of life. Epidemiological, clinical and experimental investigations have shown that anti- epileptic drugs (AED) predispose to atherosclerosis by altering the lipid profile.